Marketing Analysis of Quail Eggs in 3 Different Traditional Markets in Medan City - R.N. Putri; A. H. Daulay; A. S. Pasaribu; T. Ananta (Jurnal Peternakan Integratif, 2023)
The demand for quail eggs in several regions of Indonesia is quite high. This study aims to determine the shape of marketing channels, marketing margins, farmer's share, marketing mix and marketing efficiency of quail eggs at three different traditional markets in Medan City. The research method used is observation and interviews with respondents using a questionnaire. Sampling was done by snowball sampling technique. The results showed that the form of marketing channels for quail eggs at three different traditional markets in Medan City, there are three channels, namely: channel 1 (Farmers - Consumers), channel 2 (Farmers - Retailers - Consumers), channel 3 (Farmers - Collectors - Retailers - Consumers). Marketing margin for quail eggs in three traditional markets, the smallest on channel 1 is Rp.0 and the largest on channel 3 is Rp.64. The highest farmer's share is on channel 1 of 100% and the lowest on marketing channel 3 is 83.91%. The product marketing mix offered is quail eggs. Prices are set by retailers. Promotion uses direct promotion. Locations for trading are spread. Distribution channels directly to consumers and through intermediaries. Supporting facilities not only sell quail eggs but other products. The most efficient marketing efficient channel 1 with a value of 0%. The most efficient forms of marketing channels, marketing margins, farmer's share and marketing efficiency are in marketing channel 1. Marketing channel 1 is free of charge and marketing institutions are involved and marketing channel 1 is found in the three traditional markets in Medan City.